Towards an Adequate Anthropology - Andrzej Jastrzębski (Polonia Sacra, 2019)
An adequate anthropology is an anthropology that sees each human being as a person. It reveals fully our complexity and the fascinating dignity of human beings. ‘Adequate anthropology’ is a term proposed by John Paul II and based on three sources: The Bible, theology, and philosophy. Generally speaking, its aim consists in the defense of a large and holistic concept of our existence in opposition to all contemporary reductionistic accounts. Developing an adequate anthropology enables us to discover the very truth about ourselves. While considering the results of scientific research, it never loses sight of revelation. It is through revelation that the Creator of our being gives us the best insights into ourselves. An adequate anthropology begins by reflecting on our existential situation, which is the splintering of God’s image in us, and ends with the incarnate Word as the model of a perfect personhood.